Efficacy and safety of ciprofol versus propofol for induction and maintenance of general anesthesia: a systematic review and meta-analysis - Muhammad Hudaib; Hurais Malik; Syeda Javeria Zakir; Samra Rabbani; Dhanushan Gnanendran; Abdul Rehman Shah Syed; Noor Fatima Suri; Javeria Khan; Arham Iqbal; Nowal Hussain; Muhammad Abdullah; Satesh Kumar; et al. (Journal of Anesthesia, Analgesia and Critical Care, 2024)
Abstract Background Propofol has been the gold standard for anesthesia induction and maintenance due to its rapid onset and favorable pharmacokinetic properties. However, the search for alternative agents with improved safety and efficacy has led to the emergence of ciprofol (HSK3486), a structural analog of propofol. This systematic review and meta-analysis aim to comprehensively assess the safety and efficacy of ciprofol compared to propofol for anesthesia induction and maintenance in adult patients undergoing surgical procedures. Methods This study included only double-arm RCTs in which participants were aged eighteen or older undergoing surgery. For the statistical analysis of the extracted data, we employed RevMan 5.4.1. Results Ciprofol demonstrated a promising trend of higher anesthesiologists’ satisfaction during the induction phase (MD 0.14, 95%, CI − 0.28 to 0.56, p = 0.51), whereas Propofol was favored during maintenance. Propofol also exhibited advantages with a shorter time to successful anesthesia induction (MD 0.08 min, 95% CI 0.00 to 0.15, p = 0.04), and quicker attainment of full alertness (MD 0.11 min, 95% CI − 1.29 to 1.52, p = 0.87), suggesting its efficiency in clinical practice. Importantly, there were no significant disparities in the success rate of anesthesia. Conclusion Both ciprofol and propofol demonstrate comparable efficacy and safety for anesthesia induction and maintenance in adult patients undergoing surgery. While propofol provides a faster onset of induction, ciprofol exhibits advantages in terms of pain management. Clinicians should consider these findings when selecting anesthetic agents, and tailoring choices to individual patient needs and clinical scenarios.